Degloving Injury: Evaluation and Management - Mumtaz, Syed Naveed; Shah, Syed Fahd; Kayani, Bushra Afzal; Shah, Syed Hussain; Khan, Muhammad Wasiullah; Khan, Abdul Qadir (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the frequency, clinical presentation, management and outcome of degloving soft-tissue injuries.Study Design: Case series.Place and Duration of Study: Department of Surgery, Federal General Hospital, Islamabad Pakistan, from Jan 2018 to Dec 2019.Methodology: This study included 28 consecutive patients with degloving injuries. Patients with degloving injuries of the soft tissue were included. Initial assessments of all patients were done according to advanced trauma life support. Regular clinical examination for abnormalities such as excessive local pain that was out of line with the intensity of the trauma, extensive ecchymosis or hematomas, and especially, local and regional hypermobility of the skin, capillary refill and perfusion of the area.Results: Out of 28 patients, there were 25 males (9.28%) and three females (10.72%). The mean age was 33.07±9.04 years with a range of 6-50 years. The thigh was the most frequently involved area by degloving injury (25.00%). The back was involved in 17.85% of patients. Leg (10.71%) and foot (10.71%) were involved in 21.42% of patients. From the management point of view, 42.85% of patients had some form of debridement and healing by secondary intention, 17.85% patients were managed conservatively, and 10.71 % of the patients' primary closure was successful.Conclusion: Degloving soft-tissue injury is debilitating and, if not taken care may lead to ischemia necrosis, infection and septicemia of the tissues, which needs extensive debridement, prolonged use of broad-spectrum antibiotics, which result in disability and protracted course of rehabilitation.